The Effectiveness of Adjunct Class on The Mastery of Vocabulary And Course Content of Students of Accounting Department - Djiwandono, Patrisius Istiarto (Beyond Words, 2014)
The paper reports a classroom action research that aimed to determine the impact of a Content and Language Integrated Learning on the mastery of vocabulary and of course contents of a group of students in the Accounting Department of Universitas Ma Chung. It also intended to identify their opinions about the effectiveness of such approach. To achieve these objectives, a Time Series Design was used in a Classroom Action Research framework to introduce an adjunct class to the accounting class. The baseline data in the form of their vocabulary mastery and knowledge of the course contents were gained before the adjunct session was given. Then, the adjunct sessions were given for a period of two months. A few tests were administered to measure their progress in the mastery of vocabulary and course contents. A comparison was then drawn between the scores of the baseline data and the subsequent measures. In general, although they gained better mastery of new words, they failed to utilize them to increase their mastery of the course contents. Further exploration into the interview data reveals that most of them did not feel any significant assistance in mastering the course contents, although many of them admitted the benefit of mastering new vocabulary. There are some possible causes of the results. First, the limited duration of the adjunct sessions was felt to hinder the effectiveness. Second, the explanation in the adjunct sessions were not matched quite well with the focus during the main content course. On the basis of the results, the recommended points are the matching between the emphasis of both classes, and the lengthening of the duration of the adjunct sessions.